The effect of Laser Shock Peening on Fatigue Life Using Pure Water and Hydrofluoric Acid As a Confining Layer of Al – Alloy 7075-T6 (Journal of Engineering, 2018)
Laser shock peening (LSP) is deemed as a deep-rooted technology for stimulating compressive residual stresses below the surface of metallic elements. As a result, fatigue lifespan is improved, and the substance properties become further resistant to wear and corrosion. The LSP provides more unfailing surface treatment and a potential decrease in microstructural damage. Laser shock peening is a well-organized method measured up to the mechanical shoot peening. This kind of surface handling can be fulfilled via an intense laser pulse focused on a substantial surface in extremely shorter intervals. In this work, Hydrofluoric Acid (HF) and pure water as a coating layer were utilized as a new technique to improve the properties and to harden the treated surface of the Al -alloy 7075-T6. Fatigue life by means of laser peened workpieces was improved to 154.3%, 9.78%, respectively, for Hydrofluoric (HF) and pure water compared to un-peened specimens. And the outcomes of Vickers hardness test for laser shock peening with acid and pure water as well as un-peened specimens were 165.2HV30, 143.95HV30 and 134.7HV30, respectively showed a significant improvement in the hardness property.